Influence of direct prostheses on the condition of the alveolar processes during dental implantation - Vitaliy H. Shuturminskiy; Vasil A. Labunets; Aleksej V. Kirichek (Elsevier, 2022)
Objective: The purpose of this article is to study of the processes accompanying osseointegration of the dental implants using various plate prostheses as temporary constructions, as well as to compare the dynamics of changes in the state of the jaw alveolar processes. Materials and methods: The effect of dentures on the condition of the alveolar processes was studied in all patients according to the technique developed by L. Chulak on the 7th, 14th, 30th day and in 3, 6 months. To verify the results, the degree of atrophy of the alveolar processes was also determined by the second method the authors have chosen at the same time as indicated above. Results: The measurement results confirm linear changes in the height of the alveolar processes of the jaws with a decrease in the tissues of the prosthetic area. Throughout the duration of the examination, atrophy of the tissues of the alveolar processes is observed. Judging by the results obtained during the patients' study, it can be concluded that when applied as a temporary prosthesis with a dental delayed implantation of a partial denture made of polypropylene, the results of the state of the hard tissues of the mandible alveolar process show a better adaptation of the mucous membrane and slowing of atrophy of the jaw alveolar processes with this type of prosthetics.